Copper and carbon co-modified two-dimensional nitrogen-rich carbon nitride catalyst as well as preparation method and application thereof
By comodifying the two-dimensional nitrogen-rich carbon nitride catalyst with copper and carbon, the shortcomings of existing photocatalysts in visible light utilization and antibiotic removal are solved, and efficient photocatalytic removal effect is achieved.
Patent Information
- Application Number
- CN202411617846.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-21
AI Technical Summary
The existing photocatalysts have shortcomings in utilizing visible light, and their adsorption and removal efficiency of antibiotics are low, which limits their application in environmental pollution treatment.
The two-dimensional nitrogen-rich carbon nitride (g-C3N5) catalyst was comodified by copper and carbon, and the Cu/C-C3N5 catalyst was prepared by one-step heat condensation method, and the Cu and C modification amounts were adjusted to improve the photocatalytic performance, and the metal and non- The mutual coupling of metals expands the visible light absorption capacity and the separation and transmission of photogenerated electron-hole pairs.
The performance of the catalyst's visible light catalytic antibiotic removal is significantly improved, especially the adsorption and removal rate of tetracycline is significantly improved, and the performance is better than that of pure g-C3N5, single C modification and single Cu modification.
Smart Images

Figure CN119488929A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic materials, and in particular to a copper and carbon co-modified two-dimensional nitrogen-rich carbon nitride catalyst, and a preparation method and application thereof. Background Art
[0002] As an emerging pollutant, antibiotics have attracted the attention of many scholars in recent years. They have the characteristics of bio-resistance and environmental persistence. Traditional treatment processes generally have disadvantages such as high cost, slow reaction, easy to cause secondary pollution, and difficulty in treating low-concentration wastewater. Photocatalytic degradation has the advantages of high efficiency, energy saving, and cleanliness. It can be used as one of the methods to solve the problem of antibiotic pollution. However, existing photocatalysts generally cannot make full use of visible light and photogenerated carriers recombine rapidly, which limits the promotion and application of photocatalytic technology. In order to solve this problem, many scholars have proposed strategies for catalyst modification and adsorption-enhanced photocatalysis, which poses new challenges to the design and development of new photocatalysts.
[0003] Carbon nitride (g-C3N4) is a photocatalytic material with visible light response, which has attracted widespread attention since its advent. Carbon nitride has excellent chemical stability and unique electronic band structure, and it also has the advantages of being non-toxic, free of metal components and responsive to visible light. It is widely used in photocatalytic processes such as photocatalytic water splitting, selective photoorganic synthesis, and the elimination of organic pollutants in air or water. However, the energy gap of pure carbon nitride is about 2.7eV, and it can only use sunlight below 460nm. The polymerization product is a dense bulk particle, which has problems such as low specific surface area, weak photogenerated carrier separation ability, and poor photocatalytic activity, which limits the application range of the material. As a new type of semiconductor material, two-dimensional nitrogen-rich carbon nitride (abbreviated as g-C3N5) has become a research hotspot in recent years due to its unique composition and structure and visible light catalytic activity. Compared with g-C3N4 materials, g-C3N5 has a lower band gap width and overpotential, and a stronger ability to reduce photogenerated electrons. However, pure g-C3N5 still has the disadvantages of weak visible light absorption, high recombination rate of photogenerated carriers, and low specific surface area. Therefore, how to further improve the photocatalytic performance of g-C3N5 is a technical problem that needs to be solved urgently in the prior art. Summary of the invention
[0004] The object of the present invention is to provide a copper and carbon co-modified two-dimensional nitrogen-rich carbon nitride catalyst and a preparation method and application thereof. The copper and carbon co-modified two-dimensional nitrogen-rich carbon nitride catalyst prepared by the method provided by the present invention has excellent photocatalytic performance, a wide visible light response range, simple preparation, strong adsorption performance for the antibiotic tetracycline, and high visible light catalytic removal rate.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon, comprising the following steps:
[0007] (1) mixing 3-amino-1,2,4-triazole, copper glycinate and distilled water to obtain a mixed solution;
[0008] (2) heating the mixed solution obtained in step (1) under stirring until the water in the mixed solution is evaporated to obtain a solid precipitate;
[0009] (3) The solid precipitate obtained in step (2) is dried, ground and calcined in sequence to obtain a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon.
[0010] Preferably, in step (1), the mass ratio of 3-amino-1,2,4-triazole, copper glycinate and distilled water is 1:(0.015-0.16):10.
[0011] Preferably, the stirring rate in step (2) is 500-700 rpm, the heating temperature is 65-90° C., and the heating time is 1.0-4.5 h.
[0012] Preferably, the heating temperature is 70-85° C., and the heating time is 2.0-3.5 h.
[0013] Preferably, the drying temperature in step (3) is 80-100° C., and the drying time is 30-60 min.
[0014] Preferably, the product obtained by grinding in step (3) is in powder form.
[0015] Preferably, the heating rate of calcination in step (3) is 3.5-7.5°C / min, the calcination temperature is 400-700°C, and the calcination time is 2-5h.
[0016] Preferably, the heating rate of the calcination is 4.5-5.5° C. / min, the calcination temperature is 500-600° C., and the calcination time is 2.5-4.5 h.
[0017] The present invention also provides a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon prepared by the preparation method described in the above technical scheme.
[0018] The present invention also provides the use of the two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon as described in the above technical solution in removing tetracycline from water.
[0019] The present invention provides a method for preparing a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon, using copper glycinate as both copper and carbon sources, and 3-amino-1,2,4-triazole as a g-C3N5 precursor, and adopting a one-step thermal polycondensation method (i.e., calcination) to prepare a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon (referred to as Cu / C-C3N5), wherein the Cu and C modification amounts in the prepared catalyst are adjusted by changing the ratio of copper glycinate to 3-amino-1,2,4-triazole to improve the photocatalytic performance, and utilizing the mutual coupling of metal and non-metal, on the one hand, effectively expanding the visible light absorption capacity of the catalyst, realizing the separation and transmission of efficient photogenerated electron-hole pairs, and on the other hand, significantly improving the adsorption capacity of antibiotic tetracycline, thereby obtaining a better photocatalytic removal performance of antibiotics than pure g-C3N5, single C-modified C-C3N5 and Cu-modified Cu-C3N5 catalysts. And the method provided by the present invention has simple process, low cost, less time consumption, and can be produced quickly. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 TEM image of 0.24Cu / C-C3N5 prepared in Example 3 of the present invention;
[0021] Figure 2 HRTEM image of 0.24Cu / C-C3N5 prepared in Example 3 of the present invention;
[0022] Figure 3 XRD patterns of Cu / C-C3N5 prepared in Examples 1 to 4 of the present invention and pure g-C3N5 prepared in Comparative Example 1;
[0023] Figure 4 The XPS analysis results of 0.24Cu / C-C3N5 prepared in Example 3 of the present invention and pure g-C3N5 prepared in Comparative Example 1 are shown in FIG. Figure 4 (a) is the full spectrum. Figure 4 (b) is the high-resolution spectrum of C1s. Figure 4 (c) is the high-resolution spectrum of N1s. Figure 4 (d) is the high-resolution spectrum of Cu2p of 0.24Cu / C-C3N5;
[0024] Figure 5 UV-visible diffuse reflectance images of 0.24Cu / C-C3N5 prepared in Example 3 of the present invention, pure g-C3N5 prepared in Comparative Example 1, Cu-C3N5 prepared in Comparative Example 2, and C-C3N5 prepared in Comparative Example 3;
[0025] Figure 6The instantaneous photocurrent response diagrams of 0.24Cu / C-C3N5 prepared in Example 3 of the present invention, pure g-C3N5 prepared in Comparative Example 1, Cu-C3N5 prepared in Comparative Example 2, and C-C3N5 prepared in Comparative Example 3;
[0026] Figure 7 It is a curve diagram showing the change of the adsorption amount of tetracycline by 0.24Cu / C-C3N5 prepared in Example 3 of the present invention, pure g-C3N5 prepared in Comparative Example 1, Cu-C3N5 prepared in Comparative Example 2 and C-C3N5 prepared in Comparative Example 3 as a function of the adsorption time;
[0027] Figure 8 A comparison chart of the catalytic removal of tetracycline by Cu / C-C3N5 prepared in Examples 1 to 4 of the present invention and pure g-C3N5 prepared in Comparative Example 1 under visible light (λ≥420nm);
[0028] Fig. 9 This is a comparison chart of the catalytic removal of tetracycline by 0.24Cu / C-C3N5 prepared in Example 3 of the present invention, Cu-C3N5 prepared in Comparative Example 2, and C-C3N5 prepared in Comparative Example 3 under visible light (λ≥420nm). DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon, comprising the following steps:
[0030] (1) mixing 3-amino-1,2,4-triazole, copper glycinate and distilled water to obtain a mixed solution;
[0031] (2) heating the mixed solution obtained in step (1) under stirring until the water in the mixed solution is evaporated to obtain a solid precipitate;
[0032] (3) The solid precipitate obtained in step (2) is dried, ground and calcined in sequence to obtain a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon.
[0033] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.
[0034] The invention mixes 3-amino-1,2,4-triazole, copper glycinate and distilled water to obtain a mixed solution.
[0035] In the present invention, the mass ratio of the 3-amino-1,2,4-triazole, copper glycinate and distilled water is preferably 1: (0.01-0.2): 10, and more preferably 1: (0.015-0.16): 10. The present invention controls the mass ratio of 3-amino-1,2,4-triazole, copper glycinate and distilled water within the above range to adjust the Cu and C modification amounts, and at the same time adjust the water evaporation time to improve the preparation efficiency of the catalyst.
[0036] A mixed solution is obtained, and the mixed solution is heated under stirring until the water in the mixed solution is evaporated to obtain a solid precipitate.
[0037] In the present invention, the stirring rate is preferably 500-700 rpm; the heating temperature is preferably 65-90° C., more preferably 70-85° C.; the heating time is preferably 1.0-4.5 h, more preferably 2.0-3.5 h.
[0038] After obtaining the solid precipitate, the present invention sequentially dries, grinds and calcines the solid precipitate to obtain a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon.
[0039] In the present invention, the drying temperature is preferably 80-100°C; the drying time is preferably 30-60 minutes. In the present invention, the product obtained by grinding is preferably in powder form. The present invention grinds the sample to make it more uniform in the subsequent calcination process.
[0040] In the present invention, the heating rate of the calcination is preferably 3.5-7.5°C / min, more preferably 4.5-5.5°C / min; the calcination temperature is preferably 400-700°C, more preferably 500-600°C; the calcination time is preferably 2-5h, more preferably 2.5-4.5h. In the present invention, the crucible used for the calcination is preferably an alumina crucible. The present invention controls the heating rate, temperature and time of the calcination within the above range to obtain a better crystalline form of the copper and carbon co-modified two-dimensional nitrogen-rich carbon nitride catalyst, and the dopant will not agglomerate, thereby improving the photocatalytic activity of the copper and carbon co-modified two-dimensional nitrogen-rich carbon nitride catalyst.
[0041] After the calcination is completed, the present invention preferably grinds the calcined product to obtain a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon.
[0042] The present invention has no particular limitation on the grinding method, and a powdery copper and carbon co-modified two-dimensional nitrogen-rich carbon nitride catalyst can be obtained by using a technical solution well known in the art.
[0043] The present invention also provides a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon prepared by the preparation method described in the above technical scheme.
[0044] In the present invention, the copper-and-carbon co-modified two-dimensional nitrogen-rich carbon nitride catalyst preferably comprises two-dimensional nitrogen-rich carbon nitride, and copper and carbon supported in the two-dimensional nitrogen-rich carbon nitride.
[0045] The present invention also provides the use of the two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon as described in the above technical solution in removing tetracycline from water.
[0046] In the present invention, the antibiotic is preferably at least one of tetracycline, chlortetracycline and oxytetracycline.
[0047] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Example 1
[0049] A method for preparing a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon, comprising the following steps:
[0050] (1) Weigh 2.0 g of 3-amino-1,2,4-triazole and 0.08 g of copper glycinate and dissolve them in 20 mL of distilled water to obtain a mixed solution;
[0051] (2) heating the mixed solution obtained in step (1) at 80° C. for 3 h under stirring at a rate of 600 rpm to evaporate the water in the mixed solution to obtain a solid precipitate;
[0052] (3) The solid precipitate obtained in step (2) is completely dried in an oven at 80°C for 1 hour, and then ground into powder to obtain a solid powder. The ground solid powder is placed in an alumina crucible, placed in a muffle furnace, and the temperature is raised to 550°C at a heating rate of 5°C / min, and calcined for 3 hours. After the calcined product is completely cooled, it is taken out and ground to obtain a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon, which is recorded as 0.08Cu / C-C3N5.
[0053] The 0.08Cu / C-C3N5 prepared in Example 1 was used to degrade tetracycline in water, and the steps were as follows:
[0054] 100 mL of a 20 mg / L tetracycline aqueous solution was placed in a cylindrical quartz container with a cooling jacket, 30 mg of the 0.08 Cu / C-C3N5 photocatalyst prepared in Example 1 was added, and the mixed system was placed in a photocatalytic reaction device, the magnetic stirrer was adjusted to 600 rpm, and the mixture was stirred for 30 min in a dark environment to reach adsorption-desorption equilibrium, and then 300 μL of hydrogen peroxide was added to the photocatalytic reactor. A photocatalytic reaction was carried out under the irradiation of a visible light source (λ≥420 nm), and a liquid sample was taken every 20 min. The liquid sample was filtered through a filter (0.45 μm) to obtain a sample clear solution, and the absorbance of the sample clear solution at 358 nm was tested by a UV-visible spectrophotometer. Since the concentration of tetracycline is linearly related to its absorbance at a wavelength of 358 nm, the removal rate of tetracycline can be calculated by the absorbance at 358 nm. The test results show that after 60 minutes, the removal rate of tetracycline by 0.08Cu / C-C3N5 prepared in Example 1 is 41.3%.
[0055] Example 2
[0056] A method for preparing a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon, comprising the following steps:
[0057] (1) Weigh 2.0 g of 3-amino-1,2,4-triazole and 0.16 g of copper glycinate and dissolve them in 20 mL of distilled water to obtain a mixed solution;
[0058] The mixed solution obtained in step (1) is heated at 80° C. for 3 h under stirring at a rate of 600 rpm to evaporate the water in the mixed solution to obtain a solid precipitate;
[0059] (2)(3) The solid precipitate obtained in step (2) is completely dried in an oven at 80°C for 1 hour, and then ground into powder to obtain a solid powder. The ground solid powder is placed in an alumina crucible, and the temperature is raised to 550°C at a heating rate of 5°C / min, and the crucible is kept warm for 3 hours. After the calcined product is completely cooled, it is taken out and ground to obtain a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon, which is recorded as 0.16Cu / C-C3N5.
[0060] Under the same photocatalytic reaction conditions as in Example 1, 0.16Cu / C-C3N5 prepared in Example 2 was used to degrade tetracycline in water. The test results showed that after 60 minutes, the removal rate of tetracycline by 0.16Cu / C-C3N5 prepared in Example 2 was 74.7%.
[0061] Example 3
[0062] A method for preparing a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon, comprising the following steps:
[0063] (1) Weigh 2.0 g of 3-amino-1,2,4-triazole and 0.24 g of copper glycinate and dissolve them in 20 mL of distilled water to obtain a mixed solution;
[0064] (2) heating the mixed solution obtained in step (1) at 80° C. for 3 h under stirring at a rate of 600 rpm to evaporate the water in the mixed solution to obtain a solid precipitate;
[0065] (3) The solid precipitate obtained in step (2) is completely dried in an oven at 80° C. for 1 h, and then ground into powder to obtain a solid powder. The ground solid powder is placed in an alumina crucible, placed in a muffle furnace, and the temperature is raised to 550° C. at a heating rate of 5° C. / min, and calcined for 3 h. After the calcined product is completely cooled, it is taken out and ground to obtain a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon, which is recorded as 0.24Cu / C-C3N5.
[0066] Under the same photocatalytic reaction conditions as in Example 1, 0.24Cu / C-C3N5 prepared in Example 3 was used to degrade tetracycline in water. The test results showed that after 60 minutes, the removal rate of tetracycline by 0.24Cu / C-C3N5 prepared in Example 3 was 85.5%.
[0067] Example 4
[0068] A method for preparing a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon, comprising the following steps:
[0069] (1) Weigh 2.0 g of 3-amino-1,2,4-triazole and 0.32 g of copper glycinate and dissolve them in 20 mL of distilled water to obtain a mixed solution;
[0070] (2) heating the mixed solution obtained in step (1) at 80° C. for 3 h under stirring at a rate of 600 rpm to evaporate the water in the mixed solution to obtain a solid precipitate;
[0071] (3) The solid precipitate obtained in step (2) is completely dried in an oven at 80°C for 1 hour, and then ground into powder to obtain a solid powder. The ground solid powder is placed in an alumina crucible, placed in a muffle furnace, and the temperature is raised to 550°C at a heating rate of 5°C / min, and calcined for 3 hours. After the calcined product is completely cooled, it is taken out and ground to obtain a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon, which is recorded as 0.32Cu / C-C3N5.
[0072] Under the same photocatalytic reaction conditions as in Example 1, 0.32Cu / C-C3N5 prepared in Example 4 was used to degrade tetracycline in water. The test results showed that the removal rate of tetracycline by 0.32Cu / C-C3N5 was 64.6% after 60 minutes.
[0073] Comparative Example 1
[0074] Pure g-C3N5 was prepared in the same manner as in Example 1, except that copper glycinate was not added, and the remaining steps were the same as in Example 1.
[0075] Under the same photocatalytic reaction conditions as in Example 1, the pure g-C3N5 prepared in Comparative Example 1 was used to degrade tetracycline in water. The test results were as follows: after 60 minutes, the removal rate of tetracycline by the pure g-C3N5 prepared in Comparative Example 1 was 16.1%.
[0076] It can be seen from the above comparative examples and embodiments that the Cu / C-C3N5 prepared by the present invention effectively improves the efficiency of photocatalytic removal of tetracycline, and there is an optimal value for the amount of copper glycinate added, and 0.24Cu / C-C3N5 has the best photocatalytic performance.
[0077] Morphological structure characterization
[0078] The TEM image of 0.24Cu / C-C3N5 prepared in Example 3 was obtained by transmission electron microscopy. Figure 1 As shown, the HRTEM image of 0.24Cu / C-C3N5 prepared in Example 3 is as follows Figure 2 As shown. Figure 1 It can be seen that the g-C3N5 in 0.24Cu / C-C3N5 prepared in Example 3 is a lamellar structure, and nanoparticles with a diameter of about 10 to 20 nm are loaded on the surface of the g-C3N5 lamellar layer. Figure 2 It can be seen that the lattice spacing of the nanoparticles is 0.23 nm, corresponding to the (111) crystal plane of CuO.
[0079] The XRD patterns of Cu / C-C3N5 prepared in Examples 1 to 4 and pure g-C3N5 prepared in Comparative Example 1 were obtained by X-ray diffractometer. Figure 3 As shown by Figure 3It can be seen that all catalysts have diffraction peaks at 2θ=12.94° and 27.27°, corresponding to the (100) and (002) crystal planes of g-C3N5, respectively. In addition, with the increase of the amount of copper glycinate added, two weaker diffraction peaks gradually appear at 2θ=35.31° and 38.55°, corresponding to the (101) and (111) crystal planes of CuO, respectively. The above results show that CuO nanoclusters are formed on the surface of g-C3N5 nanosheets, and some copper ions are doped into the g-C3N5 nanosheet lattice. The weakening of the diffraction peak intensity corresponding to CuO in the XRD pattern of 0.32Cu / C-C3N5 is due to the fact that more copper ions are doped into the g-C3N5 lattice. In addition, with the increase of the amount of copper glycinate added, the diffraction peak corresponding to the (002) crystal plane of the Cu / C-C3N5 sample gradually shifted to the low angle direction, indicating that the interplanar spacing became larger, which was mainly caused by the incorporation of copper ions into the g-C3N5 lattice. The interplanar spacing of the sample modified by Cu and C becomes larger, the specific surface area will increase, and more reactive sites will be exposed on the surface of the material, which is conducive to increasing the contact area between the photocatalyst and the reactant and improving its photocatalytic efficiency.
[0080] In order to determine the elemental composition and valence state of the surface of the synthesized photocatalytic material, XPS analysis was performed on the 0.24Cu / C-C3N5 prepared in Example 3 and the pure g-C3N5 prepared in Comparative Example 1, and the XPS analysis result graphs of the 0.24Cu / C-C3N5 prepared in Example 3 and the pure g-C3N5 prepared in Comparative Example 1 were obtained. Figure 4 As shown, Figure 4 (a) is the full spectrum. Figure 4 (b) is the high-resolution spectrum of C1s. Figure 4 (c) is the high-resolution spectrum of N1s. Figure 4 (d) is the high-resolution spectrum of Cu2p of 0.24Cu / C-C3N5. Figure 4 From (a) in the figure, we can see that 0.24Cu / C-C3N5 contains four elements: C, N, O and Cu. From the high-resolution spectrum of C1s ( Figure 4 In (b), two obvious peaks were observed in g-C3N5 at 284.8 eV and 288.1 eV, corresponding to the C=C / CC bond and the sp 2 Carbon (N=C-N2). Compared with pure g-C3N5, the peak intensity at 284.8eV in 0.24Cu / C-C3N5 is significantly enhanced, which indicates that the carbon in copper glycinate is doped into the g-C3N5 lattice with C=C / CC bonds. In addition, according to the elemental analysis results, the C / N mass ratio of pure g-C3N5 is 0.55, while the C / N mass ratio of 0.24Cu / C-C3N5 is 0.57. The XPS and elemental analysis results show that C doping has been successfully completed. Figure 4 The peak of 398.6 eV in (c) can be attributed to C=NC in the heptazine ring, and the peak of 400.7 eV can be attributed to the azo double bond (CN=NC) connecting the heptazine ring or the nitrogen (C-NH2) in NH2. Figure 4 (d) is the high-resolution spectrum of Cu2p of 0.24Cu / C-C3N5, indicating that Cu has Cu + and Cu 2+ Two valence states, Cu + 2p 3 / 2 (932.9eV) and Cu 2+ 2p 3 / 2 (934.7eV), Cu + 2p 1 / 2 (952.7eV) and Cu 2+ 2p 1 / 2 (954.8eV). The above analysis results show that g-C3N5 was generated during the thermal polymerization process and Cu / C-C3N5 co-modified with Cu and C was formed.
[0081] Comparative Example 2
[0082] Single metal Cu modified g-C3N5 was prepared according to the method of Example 3 and marked as Cu-C3N5. The difference from Example 3 was that copper glycinate was replaced by a corresponding mass of copper sulfate (based on the mass of copper) according to the amount of copper glycinate in the 0.24Cu / C-C3N5 sample, and the remaining preparation steps were consistent with Example 3.
[0083] Under the same photocatalytic reaction conditions as in Example 1, the Cu-C3N5 prepared in Comparative Example 2 was used to degrade tetracycline in water. The test results showed that after 60 minutes, the removal rate of tetracycline by the Cu-C3N5 prepared in Comparative Example 2 was 47.2%.
[0084] Comparative Example 3
[0085] Non-metallic C-modified g-C3N5 was prepared according to the method of Example 3 and marked as C-C3N5. The difference from Example 3 was that the copper glycinate was replaced by the corresponding mass of glycine (based on the mass of glycine) according to the amount of copper glycinate in the 0.24Cu / C-C3N5 sample, and the remaining preparation steps were consistent with Example 3.
[0086] Under the same photocatalytic reaction conditions as in Example 1, tetracycline in water was degraded using C-C3N5 prepared in Comparative Example 3. The test results showed that after 60 minutes, the removal rate of tetracycline by C-C3N5 prepared in Comparative Example 3 was 21.1%.
[0087] It can be seen from the above embodiments and comparative examples that the photocatalytic efficiency of 0.24Cu / C-C3N5 in removing tetracycline is higher than that of Cu-C3N5 and C-C3N5 modified with a single copper source or carbon source. This is due to the synergistic effect of metal Cu and non-metal C modification, which significantly improves its photocatalytic efficiency.
[0088] Figure 5 The UV-visible diffuse reflectance images are of 0.24Cu / C-C3N5 prepared in Example 3, pure g-C3N5 prepared in Comparative Example 1, Cu-C3N5 prepared in Comparative Example 2, and C-C3N5 prepared in Comparative Example 3. Figure 5 It can be seen that compared with pure g-C3N5, Cu-C3N5 and C-C3N5, 0.24Cu / C-C3N5 has stronger absorption ability for visible light.
[0089] Figure 6 The instantaneous photocurrent response diagrams of 0.24Cu / C-C3N5 prepared in Example 3, pure g-C3N5 prepared in Comparative Example 1, Cu-C3N5 prepared in Comparative Example 2, and C-C3N5 prepared in Comparative Example 3 are shown. Figure 6 It can be seen that the photocurrent intensity of 0.24Cu / C-C3N5 is significantly greater than that of pure g-C3N5, Cu-C3N5 and C-C3N5, which indicates that the introduction of Cu and C promotes the transport of photogenerated charges and inhibits the recombination of photogenerated electrons and holes.
[0090] Figure 7 The graph is a graph showing the change in the adsorption amount of tetracycline by 0.24Cu / C-C3N5 prepared in Example 3, pure g-C3N5 prepared in Comparative Example 1, Cu-C3N5 prepared in Comparative Example 2, and C-C3N5 prepared in Comparative Example 3 over the adsorption time. Figure 7 It can be seen that the adsorption amounts of tetracycline by pure g-C3N5, C-C3N5, Cu-C3N5 and 0.24Cu / C-C3N5 were 2.04mg / g, 4.35mg / g, 7.33mg / g and 43.08mg / g respectively when the adsorption reached equilibrium in 30min. The adsorption amount of 0.24Cu / C-C3N5 was significantly higher than that of other samples, which was beneficial to the enrichment of tetracycline in the photocatalytic process, thereby improving the photocatalytic efficiency.
[0091] Figure 8 This is a comparison chart of the catalytic removal of tetracycline by Cu / C-C3N5 prepared in Examples 1 to 4 and pure g-C3N5 prepared in Comparative Example 1 under visible light (λ≥420nm). Fig. 9 This is a comparison chart of the catalytic removal of tetracycline by 0.24Cu / C-C3N5 prepared in Example 3, Cu-C3N5 prepared in Comparative Example 2, and C-C3N5 prepared in Comparative Example 3 under visible light (λ≥420nm). Figure 8 and Fig. 9 It can be seen that the tetracycline removal effect of Cu / C-C3N5 prepared in Examples 1 to 4 is significantly better than that of pure g-C3N5 prepared in Comparative Example 1, and the tetracycline removal effect of 0.24Cu / C-C3N5 is the best; the tetracycline removal effect of 0.24Cu / C-C3N5 is significantly better than that of C-C3N5 and Cu-C3N5.
[0092] In summary, compared with pure g-C3N5, C-C3N5, and Cu-C3N5, the method provided by the present invention uses Cu / C-C3N5 co-modified with Cu and C, which, on the one hand, enhances the visible light utilization rate of g-C3N5, promotes the transfer of photogenerated charges, and inhibits the recombination of photogenerated electron-hole pairs; on the other hand, the adsorption capacity of tetracycline is significantly improved, and the synergistic effect of the co-modification of Cu and C significantly improves the performance of visible light catalytic removal of tetracycline.
[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon, characterized in that: The steps include: (1) mixing 3-amino-1,2,4-triazole, copper glycinate and distilled water to obtain a mixed solution; (2) heating the mixed solution obtained in step (1) under stirring until the water in the mixed solution is evaporated to obtain a solid precipitate; (3) The solid precipitate obtained in step (2) is dried, ground and calcined in sequence to obtain a two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon.
2. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of 3-amino-1,2,4-triazole, copper glycinate and distilled water is 1:(0.01-0.2):
10.
3. The preparation method according to claim 1, characterized in that: In the step (2), the stirring rate is 500-700 rpm, the heating temperature is 65-90° C., and the heating time is 1.0-4.5 h.
4. The preparation method according to claim 3, characterized in that: The heating temperature is 70-85° C., and the heating time is 2.0-3.5 h.
5. The preparation method according to claim 1, characterized in that: The drying temperature in step (3) is 80-100° C., and the drying time is 30-60 min.
6. The preparation method according to claim 1, characterized in that: The product obtained by grinding in step (3) is in powder form.
7. The preparation method according to claim 1, characterized in that: The heating rate of calcination in the step (3) is 3.5-7.5°C / min, the calcination temperature is 400-700°C, and the calcination time is 2-5h.
8. The preparation method according to claim 7, characterized in that: The heating rate of the calcination is 4.5-5.5°C / min, the temperature of the calcination is 500-600°C, and the calcination time is 2.5-4.5h.
9. A two-dimensional nitrogen-rich carbon nitride catalyst co-modified with copper and carbon prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the copper and carbon co-modified two-dimensional nitrogen-rich carbon nitride catalyst according to claim 9 in removing antibiotics from water.